Science and technology of fast reactor safety proceedings of an international conference held in Guernsey on 12-16 May 1986. (British Nuclear Energy Society, 1987)
Proceedings of an international conference held in Guernsey in 1986.
Conference organized and sponsored by the British Nuclear Energy Society ; co-sponsored by the European Nuclear Society and the American Nuclear Society ; endorsed by the International Working Group on Fast Reactors.
Keywords: Liquid metal fast breeder reactors -- Congresses.; elektronické knihy; electronic books